Protecting Your Family and Pets from Rabies - Holly K. Ober (EDIS)
WEC239, a 4-page fact sheet by Holly K. Ober, explains what rabies is and how it spreads, which animals can get rabies, the symptoms, how common it is, how you can limit its spread, and what to do after a wild animal bite. Includes references. Published by the UF Department of Wildlife Ecology and Conservation, August 2007.